Finnish folklore atlas ethnic culture of Finland 2 (Helsinki : M. Sarmela, 2009)
Includes "99 maps on the ethnic culture of the peoples of Finland and Karelia: rites, customs, beliefs, narratives and poetry in archaic meter"--Container
Title from disc label
Includes bibliographical references
"Statistical maps drawn by Oiva Paavola ... A research project of the Academy of Finland, Research Council for Culture and Society."--P. 3
"... Suomen perinneatlas in 1994 ... while editing the English edition, I have also digitalized the Finnish version of Perinneatlas, which is published as a CD book, but it is also available as a free download on the Internet ..."--Foreword, p. 7
Maps have title: Suomen perinneatlas = Atlas of Finnish ethnic culture 2
Electronic reproduction.
Keywords: Ethnology -- Finland; Maps -- Ethnology -- Finland; Folklore -- Finland; Maps -- Folklore -- Finland; Finland -- Social life and customs